ANGLO-DUTCH CONNECTIONS IN THE EARLY MODERN WORLD - Levelt, Sjoerd. ([S.l.])
1 online resource
Keywords: This ground-breaking collection reveals the networks of interrelation between Early Modern England and the Dutch Republic. As people, ideas and goods moved back and forth across the North Sea - or spread further afield in the vanguard of globalisation and empire - Anglo-Dutch relations shaped all aspects of life, with profound implications still relevant today. A diverse range of expert scholars share new research in their discipline, ranging across technology, trade, politics, religion and the arts. Different aspects of this history of competition, alliance, migration and conflict are taken up by each chapter, providing the reader with detailed case studies as well as the broader background and its historical roots. Anglo-Dutch Connections in the Early Modern World aims to be both accessible and innovative. It will be essential to students and researchers interested in European politics, intellectual history, and shared Anglo-Dutch society, while showcasing current research in multiple facets of the Early Modern World.